High-rate wireless personal area networks. - Karaoguz, J. (IEEE Communications magazine)
This article presents an overview of high-rate wireless personal area networks, its targeted applications, and a technical overview of medium access control and physical layers, and system performance. The high-rate WPANs operate in the unlicensed 2.4 GHz band at data rates up to 55 Mb/s that are commensurate with distribution of high-definition video and high-fidelity audio. An industry effort to create a MAC and PHY layer standard specification for high-rate WPANs has been ongoing in the IEEE 802.15.3 High Rate WPAN Task Group